Selected physical correlates of agility in male A-division rugby league players - Kootshabe, K.; Onyewadume, I. U. (African Journal for Physical, Health Education, Recreation and Dance, 2018)
The purpose of this study was to examine the relationship of speed, muscle power, muscle strength and percent body fat with agility performance in male A-division rugby players based in Gaborone, Botswana. Simple random sampling technique was used to select eighty participants from the estimated population of one hundred A-division league rugby players in Botswana. Testing took place over a 3-day period for each of the four teams. On the first day, height, body mass, agility and speed were tested. On the second testing day, muscle strength and skinfolds were taken. Muscle power test was done on the third day. All measurements were taken at the University of Botswana Exercise Physiology Laboratory, the University of Botswana stadium and gymnasium of Botswana Defence Force. Pearson Product-Moment Correlation coefficients were computed to examine the relationships between agility and the physical variables. The players` agility was not significantly related to their speed, leg muscle power and leg muscle strength (p>0.05). In contrast, significant relationship was found between agility and percent body fat (p<0.05). The findings have implications for rugby training and competition, and emphasise the need for physical trainers and coaches to encourage their players to decrease body fat percentage in an attempt to maximise the efficiency of their performances in agility-intense aspects of competitive rugby.